Potensi Kulit Kayu Sebagai Sumber Serat Alam untuk Penguat pada Biokomposit yang Ramah Lingkungan dan Terbarukan: Artikel Review - Yoan Perima; Rahmat Iman Mainil (SURYA TEKNIKA, 2024)
The increasing awareness of environmental issues has influenced the use of eco-friendly materials, one of which is the use of natural fibers in biocomposites. Plant fibers are one of the sources of natural fibers that can be used as reinforcement in polymer matrix composites. Various studies have been conducted on many types of plants to explore sources of natural fibers. One natural fiber that has potential as a reinforcement in biocomposites is fiber from bark. In terms of physical and chemical properties, bark fibers can meet the criteria for reinforcement in polymer matrix composites. The tensile strength of single fibers from various types of bark ranges from 243.94 MPa to 1608 MPa. When compared to other natural fibers, such as ramie fiber with a tensile strength of 408 MPa and areca palm petiole fiber with 104.12 MPa, it can be concluded that bark fibers are equivalent to or even stronger than several other types of natural fibers. This review aims to provide background and information about the potential of bark fibers through several characterizations and tests, allowing for conclusions to be drawn regarding the feasibility of bark fibers as reinforcement in polymer matrix composites.